La fabrique de l’histoire des relations entre l’État russe et « ses » émigrés - Olga Bronnikova (Temporalités)
Since 2011-2012, Russian migrant groups in France have experienced various forms of political mobilization: on the one hand, a mobilization resulting from the protest movements against the electoral fraud in Russia, and, on the other hand, a mobilization in reaction to the Russian State’s policies towards “its” émigrés (the so-called compatriots policies). History and the past play a crucial role in this process. Russian authorities use key historical concepts and events in order to build a consensual vision of history, then "imposed" on the migrants who are perceived as spokespersons for the Russian authorities in the host country. Such a conception of history however, is fraught with contradictions that are both internal and relative to the migrants’ own subjective temporalities. These subjective temporalities provide counterpoints and forms of contestation, more or less explicit, of the standardized historical narrative that Russian authorities intend to put across. This form of subjectivity is manifested through various forms of identification with the 1990s in Russia, generally depicted in official political discourses as the “dark years”.